Recent Publications (Quarterly Journal of Economics, 1959)
Recent Publications Get access The Quarterly Journal of Economics, Volume 73, Issue 3, August 1959, Pages 510–512, https://doi.org/10.1093/qje/73.3.510 Published: 01 August 1959